Beyond metaphor drawings to envisage integration of HIV & AIDS education: A self-study in primary Mathematics teacher education - Linda van Laren (Perspectives in Education, 2014)
Researchers using participatory methods that are engaging, purposeful and facilitate social change may need further pragmatic strategies to encourage the required change. Using pencil-and-paper drawings to introduce HIV & AIDS integration in a discipline such as Mathematics Education is an innovative participatory strategy to initiate change. However, following up on such innovations to encourage take-up of HIV & AIDS integration would benefit the initiative. The following research question guides this study: What pragmatic strategy could I use in pre-service Mathematics Education to further take-up of HIV & AIDS education integration in school disciplines? I explore HIV & AIDS integration in a pre-service Primary Mathematics Education module that I taught at a higher education institution in KwaZulu-Natal, South Africa, by studying the drawings and experiences of eight final-year pre-service teachers. I use a metaphor-drawing activity to disrupt the ‘comfort zone’ of teaching Mathematics, following up by providing the pre-service teachers with learner activities suitable for primary school classrooms. When asked if they were able to integrate HIV & AIDS in Mathematics classrooms, these generalist pre-service teachers appeared to rely on phase-specific teaching material in order to take up the initiative. There is a need to use innovative participatory methods to initiate change and to provide pragmatic support for this envisaged change.